FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL - Fadhillah Asri; Yusralaini Yusralaini; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to analyze factors affecting the readiness of implementation of accrual-based government accounting standards at working unit level. This study was motivated by the issuance of PP 71 of 2010 about Government Accounting Standards which will be implemented in 2015. This research is conducted on 26 working units in Pekanbaru by using questionnaires. Data used in this research was 47 data. The independent variables in this research are human resources, organizational commitment, and supporting devices. The dependent variable is the readiness of the implementation of accrual-based government accounting standards. Multiple linier regression analysis was applied to analyze the data. The statistical results indicate that factors affecting the readiness of application of accrual-based government accounting standards are human resource and supprting devices. While the organizational commitment, is not affecting the readiness of application of accrual-based government accounting standards.Keywords: readiness of implementation of accrual-based government accounting standards, human resources, organizational commitment, and supporting devices